2017
DOI: 10.1016/j.midw.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Experience with and amount of postpartum maternity care: Comparing women who rated the care they received from the maternity care assistant as ‘good’ or ‘less than good care’

Abstract: The approach to care in the Netherlands addresses the needs as outlined by NICE and WHO. Although no data exists around the impact of use on maternal infant outcomes, this approach might be useful in other jurisdictions. MCA care might be improved if the hours of MCA care were tailored, and care by multiple MCAs minimised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
(20 reference statements)
1
11
0
Order By: Relevance
“…There is a possibility that postpartum women with no formal education did not have high expectations compared to their counterparts with some form of formal education. Our result is consistent with studies conducted in Kenya [ 27 ] and the Netherlands [ 28 ]. These studies found that women with a higher level of education rated their maternity care experiences to be unsatisfactory.…”
Section: Discussionsupporting
confidence: 93%
“…There is a possibility that postpartum women with no formal education did not have high expectations compared to their counterparts with some form of formal education. Our result is consistent with studies conducted in Kenya [ 27 ] and the Netherlands [ 28 ]. These studies found that women with a higher level of education rated their maternity care experiences to be unsatisfactory.…”
Section: Discussionsupporting
confidence: 93%
“…show that the combination of these factors results in support needs at home and strategies to meet involve integrated practices and services and assistance for urgencies and emergencies, including HV and telephone support carried out by qualified professionals (16)(17) .…”
Section: Discussionmentioning
confidence: 99%
“…The HV, considered an ancient care technology, brings favorable results and is important for the family, especially in vulnerable situations such as prematurity and those that recently come out of NICU (22) . The HV establishes a closer relation with the family environment, routines, culture and attitudes towards health care (17,22) .…”
Section: Discussionmentioning
confidence: 99%
“…These benefits include increasing mother's motivation to seek adequate information related to her condition, improving mother's motivation to access health care facilities, improving mother's knowledge and improving mother and family health behavior (Balakrishnan et al, 2016;Chaves et al, 2017;Duclos et al, 2017;Rhyne & Borawski, 2014;Smith, Gold, Td, Sumpter, & Free, 2015;Spelten & Hutton, 2017). It shows the effectiveness of mobile health in providing health education to larger community quickly, cheaply and effectively by utilizing technological advances.…”
Section: Discussionmentioning
confidence: 99%